2020
DOI: 10.7150/ijms.49533
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 promotes osteoblastic differentiation of human valvular interstitial cells through the JAK3/STAT3 pathway

Abstract: Objectives : This study amied to whether IL-21 promotes osteoblast transdifferentiation of cultured human Valvular interstitial cells (VICs). Methods : We first confirmed that IL-21 alters gene expression between CAVD aortic valve tissue and normal samples by immunohistochemistry, qPCR, and western blotting. VICs were cultured and treated with IL-21. Gene and protein expression levels of the osteoblastic markers ALP and Runx2, which can be blocked by specific JAK3 inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…STAT3 is a JAK3-related TF. Knocking down STAT3 in valvular interstitial cells inhibited expression of the osteoblastic markers, alkaline phosphatase (ALP) and RUNX family transcription factor 2 (RUNX2), and decreased matrix calcium deposition after pro-calcific stimulation ( 71 ). Moreover, p-STAT3 was also upregulated in calcified aortic valves and has clinical potential to inhibit the progression of valve calcification in an inflammatory milieu ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 is a JAK3-related TF. Knocking down STAT3 in valvular interstitial cells inhibited expression of the osteoblastic markers, alkaline phosphatase (ALP) and RUNX family transcription factor 2 (RUNX2), and decreased matrix calcium deposition after pro-calcific stimulation ( 71 ). Moreover, p-STAT3 was also upregulated in calcified aortic valves and has clinical potential to inhibit the progression of valve calcification in an inflammatory milieu ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown increased IL-6, IL-21, IL-27, and IL-33 in PAP lesions [28-30], which is in accordance with the results presented here. These cytokines have also been shown to have osteogenic activity [31][32][33][34]. Among the seven cytokines that we found reduced in PAP lesions, IL-9, IL-23, and TNFα have previously been found to be increased in PAP lesions [28].…”
Section: Discussionmentioning
confidence: 59%
“…We quantified the mRNA expression of STAT3 throughout adipogenesis, and we verified that its expression increases significantly after three days of induction and maintains this pattern until day 14 ( Figure 4(b) ). Liu et al (2020) have demonstrated that IL21 can promote osteogenic differentiation by activating JAK3/STAT3 pathway in human valvular interstitial cells [ 35 ]. Therefore, we questioned whether IL21R had any role in the differentiation process.…”
Section: Resultsmentioning
confidence: 99%